Sosialisasi dan Edukasi Pencegahan Nyeri Punggung Bawah (Low Back Pain) - Dedi Irawandi; Nuh Huda; Christina Yuliastuti; Ceria Nurhayati; Nur Muji Astuti; Imroatul Farida; Dul Majid; Sri Wahyu Wilujeng; Andan Peristika Didayana (Universitas Merdeka Surabaya, 2025)
LBP is an abbreviation for Low Back Pain, or in Indonesian known as lower back pain or lower back pain, which is a feeling of pain, soreness, or stiffness in the back area between the last rib to the buttocks, which can be caused by problems with the muscles, nerves, spine, or surrounding soft tissue. Several factors associated with the occurrence of low back pain include muscle problems, heavy activity, incorrect posture, spinal structure problems (pinched nerves, spinal stenosis, scoliosis, spondylolisthesis), arthritis, injuries, infections, tumors, kidney stones, and other medical conditions such as endometriosis and stress, triggered by risk factors such as obesity, lack of exercise, and age. Based on observations and observations in the fishing community in Gisik Cemandi Village, it was found that more than 60.7% of fishermen suffer from low back pain. Through a community service program, outreach and education about low back pain and low back pain exercises were carried out, aimed at increasing public knowledge about low back pain and low back pain exercises. The education and Low Back Pain exercises that have been carried out have had a positive impact on the health of the community in the area where previously the community did not understand how to prevent and the signs and symptoms of low back pain, as well as the movements of Low Back Pain exercises.